Theoretical Aspects of the Building Professional Competences of the Hospitality Industry Specialists - Silicka, Inese; Ļubkina, Velta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The theoretical aspects of the concept of the professional competences of future hospitality industry specialists are examined and analysed in the paper. The study is carried out within the framework of development of the doctoral thesis “Interrelation of the professional competence theories and the practice in the hospitality industry”. The components and constituent elements of the professional competences of the hospitality industry specialists are defined in the research; the concepts “professional independence” and “professional mobility” are defined.